Development of a Corpus-Based Arabic Idiom Dictionary as Communicative Learning Media for Arabic Language Students - Nafisatul Izza R.U.; Mohammad Ahsanuddin; Hanik Mahliatussikah; Salih Eltingari; Zhang Sicheng (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2026)
This research developed the use of the “Al-Misbah” digital dictionary of Arabic idioms, grounded in corpus linguistics, as a communicative learning medium for students in the Arabic Language Study Program. The background is a low level of idiomatic understanding and limited systematic and contextual learning materials. The development followed the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Idiom data were analyzed using Sketch Engine, designs were created in Figma, and applications were developed in Flutter. The validation of material and media experts showed very high feasibility (99.13% and 98%), while the student practicality questionnaire reached 85.94%. The app is interactive, user-friendly, data-driven, contextual, and flexible for advanced development. Al-Misbah offers innovative solutions for the study of Arabic idioms in an independent, communicative, and contextual manner, thereby facilitating their understanding and application across diverse contexts.